Persepsi, Pengetahuan, dan Sikap Tentang Obat terhadap Mahasiswa Universitas Tadulako di Palu, Sulawesi Tengah - Rizkika Nabila R. Makka; Amelia Rumi; Firdawati Amir Parumpu (Syntax Corporation Indonesia, 2021)
Medicine is a compound that is used for the prevention and cure of disease. Besides having benefits, drugs also have side effects, namely the cause of making mistakes in self-medication. Irrational use of drugs such as drug abuse is one of the impacts of the low knowledge of students about drugs. This study aims to assess the perceptions, knowledge, and attitudes of Health and Non-Health Students of Tadulako University in the city of Palu regarding medicine. The research was conducted by using descriptive and analytic methods with cross-sectional method using Google Form questionnaire with 345 health students and 395 non-health students. Data were analyzed using univariate and bivariate analysis using the chi-square test. The results showed that the perception of Health Students towards drug safety was categorized as high (88.7%) while Non-Health Students (72.4%), Health students having knowledge of medicine was categorized as good (94.2%) while Non-Health Students had good knowledge. good (86.3%), and Health Students were positive (64.6%) but Non-Health Students were negative (55.7%). In Health Students there is a relationship between perception and attitude (0.000 <0.05), a relationship between perception and knowledge (0.008 <0.05) and a relationship between attitude and knowledge (0.019 <0.05). Meanwhile, non-health students have a relationship between perception and attitude (0.000 <0.05), but there is no relationship between perception and knowledge (0.849> 0.05) and the relationship between attitude and knowledge (0.972> 0.05). This shows that low perceptions and knowledge can encourage students to make more fatal mistakes such as drug abuse or irrational drug use.